Chronic exposure to imipramine induces a switch from depression-like to mania-like behavior in female serotonin transporter knockout rats: role of BDNF signaling in the infralimbic cortex - Sadighi, Mina; Mai, Lingling; Xu, Yifan; Boillot, Morgane; Targa, Giorgia; Mottarlini, Francesca; Brambilla, Paolo; Gass, Peter; Caffino, Lucia; Fumagalli, Fabio; Homberg, Judith R. (Journal of affective disorders, 2024)
Background - Bipolar disorder (BD) is a highly burdensome psychiatric disorder characterized by alternating states of mania and depression. A major challenge in the clinic is the switch from depression to mania, which is often observed in female BD patients during antidepressant treatment such as imipramine. However, the underlying neural basis is unclear. - Methods - To investigate the potential neuronal pathways, serotonin transporter knockout (SERT KO) rats, an experimental model of female BD patients, were subjected to a battery of behavioral tests under chronic treatment of the antidepressant imipramine. In addition, the expression of brain-derived neurotrophic factor (BDNF) and its downstream signaling was examined in the prefrontal cortex. - Results - Chronic exposure to imipramine reduced anxiety and sociability and problem-solving capacity, and increased thigmotaxis and day/night activity in all animals, but specifically in female SERT KO rats, compared to female wild-type (WT) rats. Further, we found an activation of BDNF-TrkB-Akt pathway signaling in the infralimbic, but not prelimbic, cortex after chronic imipramine treatment in SERT KO, but not WT, rats. - Limitations - Repeated testing behaviors could potentially affect the results. Additionally, the imipramine induced changes in behavior and in the BDNF system were measured in separate animals. - Conclusions - Our study indicates that female SERT KO rats, which mirror the female BD patients with the 5-HTTLPR s-allele, are at higher risk of a switch to mania-like behaviors under imipramine treatment. Activation of the BDNF-TrkB-Akt pathway in the infralimbic cortex might contribute to this phenotype, but causal evidence remains to be provided.
Online verfügbar: 26. Januar 2024, Artikelversion: 31. Januar 2024
Gesehen am 25.07.2024